Screening for non-communicable diseases - Christe, D. M.; Vijaya, S.; Tharangini, K. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: This study was conducted to enumerate the results of screening for non-communicable diseases in the NCD clinic over a period of one year in a tertiary health centre. Methods: The results from screening tests conducted in the NCD clinic, for detecting hypertension, diabetes mellitus, breast cancer and cervical cancer, in Government tertiary care Hospital for Women, Chennai, were recorded. The flowchart and screening methods followed were those recommended by the NHM - NPCDCS. Data thus obtained was analyzed using standard statistical methods. Results: Of 42,519 women screened for common non communicable diseases - hypertension, diabetes mellitus, breast cancer and cervical cancer, nearly 5.55% women (n = 2359) had positive results, for any one of the diseases screened. Of 11,708 women screened for diabetes mellitus and 13,971 screened for hypertension, positive results were found in 856 women and 1,216 women respectively. Around 7,568 women were screened for cervical cancer and 175 women tested positive. A large number of 9,272 women were screened for breast cancer and 112 women had positive results. As per the guidelines, women who tested positive for screening tests were referred to the concerned departments in RGGGH. Conclusions: Nearly 42,519 women were screened for common non-communicable diseases (NCDs) - hypertension, diabetes mellitus, breast cancer and cervical cancer, and 5.55% women had positive test results for any one of the diseases screened. The screening revealed, 8.7% of women had raised blood pressure, 7.31% had raised blood sugar levels, 1.21% women had positive screening test results for breast cancer, and 2.31% women for cervical cancer.